Point de mire ou rythme du pire, la semaine comme temporalité paradoxale chez Flaubert - Marie-Astrid Charlier (Flaubert: Revue Critique et Génétique)
In his novels on contemporary mores Flaubert develops a poetics of modern times in which the weekly rhythm crystallizes temporal experiences that are a priori opposed. Between rite and duration, the motif of the week appears either as a support for the representation of the bourgeois mechanism - temporal, intellectual, moral -, or literally as a vanishing point toward romance and adventure. With the microanalysis of several of Flaubert’s weeks, we shall strive to show that in Madame Bovary and L’Éducation sentimentale they convey densities of time and synthesize the complexity of real time, consisting of layering, persistences, projections, erasings. Flaubert’s week also raises the issue of the relations between historical, social, and private time.